Journey into the unknown: considering the international medical graduate perspective on the road to Canadian residency during the COVID-19 pandemic. - Gutman, Arlene; Tellios, Nikoleta; Sless, Ryan Taylor; Najeeb, Umberin (Canadian Medical Education Journal, 2020)
The COVID-19 pandemic has had a tremendous effect on education programs worldwide, including medical education. Particularly, International Medical Graduates (IMGs) planning to pursue residency training in Canada have been profoundly impacted. Cancellation of away electives, as well as changes to the format, timeline, and requirements of mandatory medical licensing exams has left IMG residency applicants in uncharted territory. Given that IMGs comprise up to 25% of the Canadian healthcare force, and often are based in underserviced areas, the licensure and eligibility of IMGs to continue to enter the Canadian healthcare force is of the utmost importance in the midst of the COVID-19 pandemic. As the pandemic evolves, it is imperative that key decision makers and stakeholders continue to consider the downstream effect for IMGs and their eligibility to practice in Canada.